Description of D‐glucosamine immobilization kinetics onto poly(lactic acid) surface via a multistep physicochemical approach for preparation of novel active biomaterials. Issue 11 (15th September 2017) - Swilem, Ahmed E.; Lehocký, Marian; Humpolíček, Petr; Kucekova, Zdenka; Novák, Igor; Mičušík, Matej; Abd El‐Rehim, Hassan A.; Hegazy, El‐Sayed A.; Hamed, Ashraf A.; Kousal, Jaroslav
Abstract: Poly(lactic acid) (PLA) has shown much success in the preparation of tissue engineering scaffolds as it can be fabricated with a tailored architecture. However, the PLA surface has drawbacks including the lack of biofunctional motifs which are essential for high affinity to biological cells. Therefore, this study describes a multistep physicochemical approach for the immobilization of d ‐glucosamine (GlcN), a naturally occurring monosaccharide having many biological functions, on the PLA surface aiming at enhancing the cell proliferation activity. In this approach, poly(acrylic acid) (PAAc) spacer arms are first introduced into the PLA surface via plasma post‐irradiation grafting technique. Then, covalent coupling or physical adsorption of GlcN with/on the PAAc spacer is carried out. Factors affecting the grafting yield are controlled to produce a suitable spacer for bioimmobilization. X‐ray photon spectroscopic (XPS) analyses confirm the immobilization of GlcN on the PLA surface. The XPS results reveal also that increasing the yield of grafted PAAc spacer on the PLA surface increases the amount of covalently immobilized GlcN, but actually inhibits the immobilization process using the physical adsorption method. Contact angle measurements and atomic force microscopy (AFM) show a substantial increase of surface energy and roughness of PLA surface, respectively, upon the multistep modification procedure. The cytocompatibility of the modified surfaces is assessed using a mouse embryonic fibroblast (MEF) cell line. Observation from the cell culture basically demonstrates the potential of GlcN immobilization in improving the cytocompatibility of the PLA surface. Moreover, the covalent immobilization of GlcN seems to produce more cytocompatible surfaces if compared with the physical adsorption method. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 3176–3188, 2017.